Revision of the Histopona italica group (Araneae: Agelenidae), with the description of two new species - Bolzern, Angelo; Pantini, Paolo; Isaia, Marco (Zootaxa, 2013)
During a large survey of agelenid spiders from different private and museum collections, a closer examination of material from all over Italy (including type material and fresh material) previously identified as Histopona italica Brignoli 1977, disclosed two new species for science, both belonging to the italica group. Based on the results of the present work, we describe Histopona leonardoi sp. n. and H. fioni sp. n. and revise the distribution pattern of H. italica group in Italy and Switzerland. Drawings and photographs of relevant structures and a table summary of the diagnostic characters allowing a fast separation of the species are provided.